Capacitive Performances of Reduced Graphene Oxide Hydrogel Prepared by Using Sodium Hypophosphite as Reducer. Issue 1 (28th October 2015) - Liu, Cuixian; Han, Gaoyi; Chang, Yunzhen; Xiao, Yaoming; Li, Yanping; Li, Miaoyu; Zhou, Haihan
Abstract: The hydrogels of reduced graphene oxide (rGOHGs) have been synthesized through treating GO with various concentrations of sodium hypophosphite (NaH2 PO2 ) under hydrothermal condition. The results reveal that the structure of rGOHGs changes along with the increase of the concentration of NaH2 PO2 . The rGO sheets prepared with low concentration of NaH2 PO2 exhibit more crimples and larger specific surface area than those prepared with high concentration of NaH2 PO2 . The measurements of the capacitive performances of rGOHGs reveal that the rGOHGs prepared with low concentration of NaH2 PO2 possess larger specific capacitance ( C s ) than that prepared with high concentration of NaH2 PO2 at low cyclic voltammetry scan rates. However, the rGOHGs prepared with high concentration of NaH2 PO2 possess larger C s at high scan rates, more stability and better high‐rate capability than those prepared at low concentration. It is believed that the structures and properties of rGOHGs can be adjusted by controlling the concentration of NaH2 PO2 according to the requirement. Abstract : Hydrogels of reduced graphene oxide (rGOHGs) were synthesized by using sodium hypophosphite as reducing reagent. The rGOHGs prepared with different concentrations of NaH2 PO2 exhibit different microstructures and capacitive properties, some have larger specific capacitance and some have high‐rate capability.